Konsep Jiwa Perspektif Ibnu Miskawaih - Mahrus Fauzani (Mazalat: Jurnal Pemikiran Islam, 2025)
Ibn Miskawaih, a prominent Muslim philosopher, offers an in-depth view of the concept of the soul which is foundational to Islamic philosophy of ethics and psychology. In his thinking, the human soul is a non-material entity that has the potential to develop and achieve perfection. According to Ibnu Miskawaih, the human soul has three main aspects, namely the rational, emotional and lustful aspects. All three play a role in determining individual behavior and character. The rational aspect is considered the highest element in the structure of the soul, because it has the ability to understand truth, reflect on meaning, and direct humans towards higher moral goals. Meanwhile, the emotional aspect functions to control lustful impulses which are often instinctive and irrational. Through a balance between these three aspects, humans can achieve true happiness which according to Ibn Miskawaih can only be obtained through moral and intellectual perfection. Ibnu Miskawaih also emphasized the importance of education and mental training to form noble morals. Through good habits, humans can strengthen their rational aspects so that they are able to control emotional impulses and desires. This process, which he calls tazkiyah al-nafs, is the essence of human spiritual journey towards perfection. Ibn Miskawaih's view of the soul provides a comprehensive philosophical framework for understanding the relationship between morals, reason and spirituality in human life. His philosophy remains relevant as a guide to self-development and ethics in a modern context.